Analisis Kesenjangan Persepsi Nelayan Dan Pelaksana Teknis Terhadap Keberadaan Kebijakan Perikanan Tangkap Di Desa Muara Gading Mas, Kecamatan Labuhan Maringgai, Kabupaten Lampung Timur - Rizka Helisia Putri; Abdullah Aman Damai; Supono Supono; Indra Gumay Febryano; Hengky Mayaguez (Journal of Tropical Marine Science, 2023)
The capture fisheries sector has an important role for the economy in coastal areas. Appropriate policy programs are needed to support a sustainable capture fisheries sector. The purpose of this study is to analyze public and government perceptions of the existence of policy programs related to capture fisheries in Muara Gading Mas Village, Labuhan Maringgai District, East Lampung Regency. Data collection was carried out by observation and interviews using a questionnaire. The data was analyzed by the perception of the relationship with the Likert scale on policy objectives, policy success, policy implementers, policy supervisors and infrastructure and the environment. The results shows that there is a discrepancy between fishermen's perceptions and technical implementers due to the distrust of the two implementers towards the management of capture fisheries policies in order to develop Muara Gading Mas Village. To overcome this perception gap, behavioral engineering (social engineer) is needed for fishermen through the establishment of cooperatives/business entities that are licensed and supported by the government as subjects and vessels for fishermen to borrow capital to break the chain of the patron client system in Muara Gading Mas Village.